Evaluation of the knowledge and attitudes about hypospadias of the parents of children diagnosed with hypospadias: A qualitative study - ÇÖVENER ÖZÇELİK, ÇAĞRI (My University, 2024)
Purpose: The purpose of the study to determine the knowledge and attitudes of the parents of children diagnosed with hypospadias. Methods: This descriptive study conducted on the families of children diagnosed with hypospadias and discharged from a pediatric surgery clinic in a state hospital in Istanbul between April 2018 and December 2018. Data collected with parent information form, type recorder, semi-structured interview. Content analysis was used to evaluate the qualitative data. Research results are reported according to the COREQ Checklist. Results: After analyzing the interviews of the participants, eight themes have been created: “Inaccuracy of information about hypospadias”, “The fact that the information is not clear and understandable by the family”, “Anxiety about the surgery and the prognosis of the disease in the pre-operative period”, “Fears about the process and after the surgery”, “Positive emotions after surgery", "Negative emotions after surgery", "Supporting post-operative care", "Importance of cosmetic appearance", Conclusion: It was found that the parents did not have enough information about hypospadias and the postoperative process adversely affected the attitudes of the parents towards the disease. Keywords: Attitude; children; parents; hypospadias.

Giriş: Hipospadias 300 doğumda bir görülen konjetinal doğum anomalisidir. Toplumda görülme sıklığının fazla olması nedeniyle bu hastalığa sahip olan ailelerin bilgi ve tutumlarının bilinmesi önem taşımaktadır. Amaç: Araştırma hipospadiaslı çocuğu olan ailelerin bilgi ve tutumlarının incelenmesi amacıyla yapılmıştır. Yöntem: Tanımlayıcı olan araştırma Nisan 2018-Aralık 2018 tarihleri arasında İstanbul’da bir eğitim araştırma hastanesinin çocuk cerrahisi kliniğinden taburcu olmuş 31 hipospadiaslı çocuğun ebeveyni ile yapılmıştır. Veri toplama aracı olarak; Ebeveyni Tanıtıcı Bilgi Formu, Ses Kayıt Cihazı, Yarı Yapılandırılmış Görüşme Formu kullanılmıştır. Niteliksel verileri değerlendirmek için içerik analizi yapılmıştır. Araştırma sonuçları COREQ Checklist’e göre raporlanmıştır. Bulgular: Katılımcıların görüşmeleri çözümlenmiş ve sekiz adet tema oluşturulmuştur: “Hipospadias Hakkında Doğru Bilgiye Sahip Olmama”, “Yapılan Bilgilendirmenin Aile Tarafından Açık ve Anlaşılır Bulunmaması”, “Ameliyat Öncesi Dönemde Ameliyat ve Hastalığın Prognozuna İlişkin Anksiyete”, “Ameliyat Süreci ve Sonrasına İlişkin Korkular”, “Ameliyat Sonrası Olumlu Duygular”, “Ameliyat Sonrası Olumsuz Duygular”, “Ameliyat Sonrası Bakımın Desteklenmesi”, “Kozmetik Görünümün Önemi”. Sonuç: Ebeveynlerin hipospadiasla ilgili yeterli bilgiye sahip olmadıkları, ameliyat sonrası sürecin ebeveynlerin hastalığa karşı olan tutumlarını olumsuz etkilediği saptanmıştır. Anahtar Kelimeler: Aile; çocuk; hipospadias; tutum.
Keywords: Hemşirelik; Çocuk Sağlığı ve Hastalıkları Hemşireliği; Sağlık Bilimleri; Nursing; Child Health and Diseases Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Aile; çocuk; hipospadias; tutum; Attitude; children; parents; hypospadias